Crystal engineering with pyrazolyl-thiazole derivatives: structure-directing role of π-stacking and σ-hole interactions - Ahmed, Muhammad Naeem (2021)
The synthesis and X-ray characterization of 1-(2-(3-(4-bromophenyl)-5-(4-methoxyphenyl)-4,5-dihydro-1H-pyrazol-1-yl)-4-methylthiazol-5-yl)ethanone (7), ethyl 2-(5-(4-bromophenyl)-3-(4-chlorophenyl)-4,5-dihydropyrazol-1-yl)thiazole-4-carboxylate (8) and 2-(5-(4-chlorophenyl)-3-phenyl-4,5-dihydro-1H-pyrazol-1-yl)-N′-(2-hydroxy-3-methoxybenzylidene)thiazole-4-carbohydrazide (10) are described in this manuscript. The structure-directing role of a variety of noncovalent interactions has been analyzed energetically using DFT calculations and Hirshfeld surface analysis. Moreover, the existence and importance of halogen and chalcogen bonding interactions have been analyzed by using the quantum theory of atoms in molecules and the noncovalent interaction index (NCIplot).